2017
DOI: 10.1016/j.bmc.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of emetine prodrugs that are proteolytically activated by the prostate specific antigen (PSA) and evaluation of in vivo toxicity of emetine derivatives

Abstract: Emetine is a small molecule protein synthesis inhibitor that is toxic to all cell types and therefore suitable for complete killing of all types of heterogeneous cancer cells within a tumor. It becomes significantly inactive (non-toxic) when derivatized at its N-2′ secondary amine. This provides a strategy for targeting emetine to cancerous tumor without killing normal cells. In this report, PSA activatable peptide prodrugs of emetine were synthesized. To overcome steric hindrances and enhance protease specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…However, these clinical studies did not lead to the clinical application of emetine as they revealed only marginal efficacy and some adverse side effects, such as cardiac damage. In recent years, derivatives of emetine have been synthesized and reported to offer better efficacy against cancer cells along with less toxicity to normal cells (17,18). Moreover, various studies have demonstrated a potent cytotoxic activity of emetine and its biological targets in a variety of human carcinoma cell lines (19–24).…”
Section: Introductionmentioning
confidence: 99%
“…However, these clinical studies did not lead to the clinical application of emetine as they revealed only marginal efficacy and some adverse side effects, such as cardiac damage. In recent years, derivatives of emetine have been synthesized and reported to offer better efficacy against cancer cells along with less toxicity to normal cells (17,18). Moreover, various studies have demonstrated a potent cytotoxic activity of emetine and its biological targets in a variety of human carcinoma cell lines (19–24).…”
Section: Introductionmentioning
confidence: 99%
“…Эметин является основным алкалоидом ипекакуаны, или рвотного корня -травянистого растения семейства Мареновых рода Carapichea. Он ингибирует синтез белка в эукариотических клетках путем необратимого блокирования движения рибосом вдоль цепи мРНК за счет ингибирования переноса пептидил тРНК из акцепторного в донорный сайт рибосомы [11]. В недавних исследованиях было показано, что эметин индуцирует апоптоз за счет повышения экспрессии генов проапоптотических факторов (антагонист-киллер Bcl-2 (BAK1), каспаза 8, каспаза 9, ассоциированный с клеточной гибелью белок DAXX, гранзим B (GZMB)) и снижения экспрессии антиапоптотических генов (Bcl-xL, рецептор эпидермального фактора роста (EGFR), фактор некроза опухоли (TNF)) [12,13].…”
Section: Discussionunclassified
“…Methods for the synthesis and characterization of the FLASH and D-FLASH probes are presented in the Supporting Information. , …”
Section: Methodsmentioning
confidence: 99%